Efficacy and safety of polymyxins for the treatment of Acinectobacter baumannii infection: a systematic review and meta-analysis. - Qianqian Liu; Wenzhang Li; Yulin Feng; Chuanmin Tao (PLoS ONE)
Background Multi-drug resistance among Acinetobacter baumannii increases the need for polymyxins. We conducted a meta-analysis aimed to assess the efficacy and safety of polymyxins for the treatment of Acinetobacter baumannii infection. Methods We searched PUBMED, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), CNKI, Chinese Biomedical Literature Database up to November 1, 2013, to identify published studies, and we searched clinical trial registries to identify completed unpublished studies. Randomized controlled trials and cohort studies were considered for inclusion. Data were extracted on clinical response, microbiological response, mortality, length of stay and adverse events. Results 12 controlled studies, comparing 677 patients, were included. Although clinical (odds ratio 1.421, 95% confidence interval 0.722-2.797) and microbiological (OR 1.416, 95% CI 0.369-5.425) response rates favored the polymyxins group, these differences were not significant. Treatment with polymyxins vs. controls did not affect hospital mortality (OR 0.506, 95% CI 0.101-2.536), lengths of hospital stay (standard mean difference -0.221, 95% CI 0.899-0.458) or nephrotoxicity (OR 1.192, 95% CI 0.436-3.261). The combination of polymyxins with other antibiotics achieved similar clinical response rates to its monotherapy regimen (OR 0.601, 95% CI 0.320-1.130). Conclusions Our results suggest that polymyxins may be as safe and as efficacious as standard antibiotics for the treatment of A. baumannii infection. There is no strong evidence that combination regimen of polymyxins is superior to monotherapy regimen.